ANALISIS PRODUKTIVITAS TENAGA KERJA DI AREA PELABUHAN (STUDI PADA PT. ASDP WILAYAH KERJA KAYANGAN LOMBOK TIMUR) - ARI PURWANTO, RENDI; PUTU WARKA, I GEDE; ASHARI, ISYA (GANEC SWARA, 2019)
This study aims to determine the effect of age, work experience, expertise of workers, health of workers, suitability of wages, field conditions and tools on the level of labor productivity in Kayangan port business and KMP Dingkis especially in cleaning services and kepil. Data analysis in this study uses the help of SPSS Software. In this study multiple linear regression analysis was conducted to determine the direction of the relationship between the independent variable and the dependent variable whether each independent variable is positively or negatively related and to predict the value of the dependent variable if the value of the independent variable increases or decreases. Data used is interval or ratio scale.     From the results of the analysis that has been carried out the level of productivity of workers in the cleaning service and kepil work at PT. ASDP East Lombok Kayangan Work Area is 85.53%, meaning that the productivity level is very good. Simultaneously age, experience, expertise. health, wage suitability, field conditions and supporting facilities have a significant effect on labor productivity, with F test (10,568)> F table (2,148). The partial dominant influence on labor productivity is: labor wages, supporting facilities, health and labor experience. This can be seen from T count> T table, while age, expertise and field conditions affect productivity but not real, because T count <T table. Simultaneously all variables have a significant effect because they have an R value or a high correlation of 0.722. The most dominant variable influencing labor productivity is wage suitability.